2017
DOI: 10.1186/s12964-016-0156-8
|View full text |Cite
|
Sign up to set email alerts
|

HECTD1 controls the protein level of IQGAP1 to regulate the dynamics of adhesive structures

Abstract: BackgroundCell migration including collective cell movement and individual cell migration are crucial factors in embryogenesis. During the spreading/migration of cells, several types of adhesive structures physically interacting with the extracellular matrix (ECM) or with another cell have been described and the formation and maturation of adhesion structures are coordinated, however the molecular pathways involved are still not fully understood.ResultsWe generated a mouse embryonic fibroblast line (MEF) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
(59 reference statements)
3
19
0
Order By: Relevance
“…Consistent with TargetScan predictions, our findings indicated that HECTD1 was a target of miR-9 based on Luciferase activity assay results. The gene encoding HECTD1 has been mapped to a region of chromosome 14q12 encoding a novel protein homologous to the E6-AP C-terminal (HECT) domain-containing E3 ubiquitin ligase, which regulates the selective ubiquitination of HSP90 client proteins [39,51]. Consistent with these findings, our study indicated that HSP90 was the target for HECTD1 ubiquitination.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with TargetScan predictions, our findings indicated that HECTD1 was a target of miR-9 based on Luciferase activity assay results. The gene encoding HECTD1 has been mapped to a region of chromosome 14q12 encoding a novel protein homologous to the E6-AP C-terminal (HECT) domain-containing E3 ubiquitin ligase, which regulates the selective ubiquitination of HSP90 client proteins [39,51]. Consistent with these findings, our study indicated that HSP90 was the target for HECTD1 ubiquitination.…”
Section: Discussionsupporting
confidence: 76%
“…In a previous study, it was demonstrated that HECT domain E3 ubiquitin ligase 1 (Hectd1) homozygous mutant embryos exhibited numerous defects in embryonic and fetal development (11) and MEF cells isolated from Hecdt1-mutant mice were observed to accelerate cell migration (12). Consistent with these observations, the present study demonstrated that the migration of human cells in which HECTD1 was knocked down (HECTD1-KD cells) was altered, which simultaneously suppressed the degradation of SNAIL.…”
Section: Introductionsupporting
confidence: 87%
“…Wound healing assay. The wound healing assay for HeLa cells was performed as previously described (12). Three independent experimental repeats were performed.…”
Section: Reverse Transcription-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…HECTD1 mediates the Lys‐63 polyubiquitination degradation of adenomatous polyposis coli (APC) to facilitate the APC‐Axin interaction (Tran et al, ). IQGAP1, one of the effectors of HECTD1, is regulated by HECTD1 through ubiquitination and therefore mediates the formation of focal adhesions (FAs) and influences cell spreading and migration (Shen et al, ). Interestingly, STK4 decreased significantly in our proteomic results, which supported the relationship between phosphorylation and ubiquitination in this infection process.…”
Section: Discussionmentioning
confidence: 99%